CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION OF WOMEN (E Conference Zone, 2022)
In this article, starting with the Universal Declaration of Human Rights, most international and national legal instruments give all women and men, girls and boys, the same rights and responsibilities as all human beings. The scholar's analysis of society's existence and existing relationships is irrelevant here.